Alternative and online weight loss interventions during Covid-19 pandemic lockdown - Woźniak, Jakub; Garbacz, Katarzyna; Wojciechowska, Olga; Włodarek, Dariusz (Roczniki Państwowego Zakładu Higieny, 2022)
The problem of obesity is affecting an increasing number of people worldwide. The COVID-19 pandemic and the required social distancing, which make it impossible to see a dietitian, present new challenges and require the development of new ways of working with overweight individuals. Based on research and practice, dietetic services are beginning to shift from in-office consultations to a form of online consultation using mobile apps and websites. This literature review aims to critically analyze the scientific evidence for the effectiveness of interventions targeting weight loss in overweight or obese individuals focusing on behavioral and online interventions. The data from the presented studies suggest that the effectiveness of online interventions to control body weight is high enough to be used in nutritional education and in weight reduction or maintenance. The main advantage is a wide access to them for the public.